In Silico Study of Alkaloids as α-Glucosidase Inhibitors: Hope for the Discovery of Effective Lead Compounds - Zafar, Muhammad; Khan, Haroon; Rauf, Abdur; Khan, Ajmal; Lodhi, Muhammad Arif (Frontiers in Endocrinology, 2016)
α-glucosidase (EC 3.2.1.20) is a primary carbohydrate metabolizing enzyme that acts on the 1-4 associated α-glucose residues. The inhibition of α-glucosidase slows down the process of carbohydrate digestion and avoids postprandial hyperglycemia, which is a major cause of chronic diabetes-associated complication. This study was designed to evaluate the binding capacity of isolated alkaloids with targetted receptor. For this purpose, the three-dimensional tertiary structure of the α glucosidase was generated by using the MOE. The generated model was then validated by using the RAMPAGE and ERRAT server. The molecular docking of 37 alkaloids along with standard acarbose and miglitol reported as a α-glucosidase inhibitor was performed via MOE-Dock implemented in MOE software to find the binding modes of these inhibitors. The results showed that compound 17 (oriciacridone F) and 24 (O-methylmahanine) demonstrated marked interaction with active residues and were comparable to standard inhibitors. In short, this study provided computational background to the reported α-glucosidase inhibitors and thus further detail studies could lead to novel effective compounds.